Effect of different finishing and polishing techniques on surface roughness of composite restorations - Mostafa, Dilruba Binte; Chowdhury, Nipu Rani; Nahar, Kulsum; Salma, M. Ummay; Jannat, Isratul; Sarmin, Shahela; Emon, Khandokar Emanuzzaman (International Journal of Research in Medical Sciences, 2026)
Background: Esthetic demands have become increasingly important in modern dentistry, and the quality of the restoration finish particularly surface roughness plays a critical role in determining the long-term clinical success of resin-based composite restorations. The purpose of the study is to evaluate the effect of different finishing and polishing techniques on the surface roughness of composite restorations. Methods: This cross-sectional study at the Department of Science of Dental, Shaheed Suhrawardy Medical College, Dhaka, Bangladesh (June 2023 to May 2024) included 100 participants receiving composite restorations, randomly assigned to Mylar strip, diamond burs, Sof-Lex discs, or multi-step polishing; surface roughness (Ra) was measured and analyzed using ANOVA and Tukey’s test (p<0.05). Results: Among 100 participants (mean age 28.5±6.0 years; 48 males, 52 females), surface roughness differed significantly across finishing techniques (p<0.001). Mylar strip produced the smoothest surfaces (0.08±0.02 µm), diamond burs the roughest (0.62±0.15 µm), and Sof-Lex discs (0.18±0.04 µm) and multi-step polishing (0.22±0.05 µm) were intermediate. Post-hoc tests confirmed significant differences between most pairs, except between Sof-Lex and multi-step (-0.04 µm, p=0.120). Conclusions: The type and sequence of finishing and polishing techniques significantly affect the surface smoothness of composite restorations, with Mylar producing the smoothest and diamond burs the roughest surfaces.